ANALISIS KELAYAKAN PEMEKARAN KECAMATAN TANA RIGHU KABUPATEN SUMBA BARAT PROVINSI NUSA TENGGARA TIMUR - Rohmadin, Sulthon; Batubara, Yusi Eva (Fakultas Politik Pemerintahan, 2017)
ABSTRACT This Article to explain about the possibility of growth feasibility of Tana Righu District, Sumba Barat Residence as PP 19/2008 about District. The analysis of growth feasibility possibility of Tana Righu District to act as possibility administrative, technical, and fisical territorial. These result, administrativelly, district of Tana Righu eligible for growth. The Tecnically, also eligible to growth. So, fisically, not eligible to growth. Keywords: feasibility, growth, technical, fisical territory, and administrative.